katG Gene association with Isoniazid Resistance in Multiple Drug Resistant Tuberculosis - Farouk Qamar Malik; Imran Ali Zaidi; Sana Hafeez; Anila Jaleel; Amna Iqtidar; Ali Raza Awan (ziauddin University, 2024)
Background: TB has been announced as a global emergency of this millennium. It is one of the leading causes of death among adults due to a single infectious agent. Pakistan is fifth among the twenty two Eastern Mediterranean Region countries with the highest burden of disease which is approximately 270 per 100,000. The emergence of drug resistant MTB poses a serious threat to the ongoing efforts to control the disease epidemic. Drug resistance to the first line drugs such as Isoniazid (INH) and Rifampicin (RIF) needs to be investigated. In this respect the role of various genes conferring resistance should be studied to find better treatment alternatives. The current practice of drug sensitivity testing requiring approximately three weeks is time consuming and a major cause of treatment delay. Objectives: The aim of the present study was to sequence the mutations in katG gene which contribute towards INH resistance and to study association of katG gene with INH resistance in MTB. Methods: In this research sputum samples were collected in wide mouth transparent containers from suspected TB patients. After decontamination samples were inoculated onto LJ medium. The colonies grown on the slopes were identified as MTB by standard biochemical test. Isolates were tested on LJ medium for in vitro DST (Drug Sensitivity Testing). MDR was described as resistance to INH and RIF with or without resistance to other drugs. DNA was extracted from the grown samples using kit method. After extraction of DNA, the region from base 2714 to 3232 of katG gene was amplified through PCR and the amplified products were sequenced. Analysis of the DNA sequences and mutations was done with the help of BLAST - alignment software. A total of 24 MDR MTB samples were sequenced. Sequence analysis revealed the reported mutation Ser → Thr in katG codon 315 in five samples (21%). In this study, an authentic molecular analysis (test) was developed and validated for identification of INH resistant strains in Pakistani population. Conclusion: It was concluded from the study that mutation of some genes particularly point mutation in codon 315 of katG gene is associated with development of resistance to the drug INH in Multi drug resistant TB.   Key words: isoniazid, multiple drug resistant tuberculosis